INTERPRETASI MAKNA SULHU DALAM PENYELESAIAN KASUS NUSYUZ SUAMI PERSPEKTIF TAFSIR - Syafi’i; Mochammad Novendri S (An Natiq, 2024)
In Islamic law domestic conflict is referred to by the term nusyuz. The concept was taken from the Q.S. An-Nisa': 34 and 128. From this verse, when a comparison is made between the wife's nusyuz settlement and the husband, there is a difference in settlement pattern, both of which indicate discrimination against the wife. Therefore, it is necessary to examine the meaning of the sulhu in depth by interpreting the meaning of the sulhu in the settlement of the case from the nusyuz husband's interpretation perspective. This study used the content analysis method, a research technique to draw conclusions from legitimate data by considering the context. As for the results of this study, the reason for using the word "sulhu" in the settlement of the nusyuz husband is because it gives the parties freedom and opportunity to think about the best way to resolve their disputes even to cancel each other's rights from the latter, so that they can be able to do so. satisfying the parties to the dispute, bringing peace of mind and strengthening the bonds of friendship. In the settlement of the nusyuz wife according to the duties of a man in the family is as a leader who aims to protect and protect his family by educating and teaching it. As for the nusyuz husband, by way of sulhu (peace). Even when viewed from the asbabun-nuzul verse it is only one example of completion of the sulhu. Furthermore, the wife can also choose another way in order to benefit both. Which is essentially that sulhu is a very wise way for women to solve the nusyuz husband problem in the various ways they agree. It means that it is not true that sulhu makes women's position weak or there is discrimination against women, but sulhu is actually glorifying women themselves.